Optimizing The Strengthening Of Lecturer’s Professional Commitment Based On Local Wisdom And Organizational Support - Fitri Anjaswuri; Soewarto Hardhienata; Suhendra Suhendra (Journal of International Multidisciplinary Research, 2025)
This study aims to construct an integrated constellation model and determine optimal strategies for reinforcing lecturers’ professional commitment at leading private universities in Bogor. Utilizing the POP-SDM (Modeling and Optimization of Management Resources) framework, the research integrates elements of local wisdom and organizational support within a systemic approach to human resource development. The exploratory qualitative phase involved in-depth interviews and focus group discussions to uncover major determinants influencing professional commitment. From the thematic analysis, four principal variables emerged—teamwork, organizational climate, religiosity, and work motivation—which were validated through expert judgment. Quantitative verification was subsequently performed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique to examine both direct and indirect relationships among constructs. The analysis confirmed that all variables exert positive and significant effects on lecturers’ professional commitment, with work motivation being the most dominant factor. To refine improvement priorities, the SITOREM (Scientific Identification Theory for Conducting Operational Research in Educational Management) method was applied, identifying indicators that should be improved, maintained, or further developed. The findings offer empirical and practical insights, including: (1) a validated POP-SDM–based commitment model combining cultural and organizational dimensions; (2) evidence-based strategies to enhance lecturer professionalism; and (3) an optimization framework to guide sustainable lecturer development in higher education institutions.